2022
DOI: 10.1002/pchj.583
|View full text |Cite
|
Sign up to set email alerts
|

Dual role of empathy in job stress, burnout, and intention to leave among addiction specialists

Abstract: This study aimed to investigate the relationship between job stress, burnout, and intention to leave, moderated by empathic concern and perspective‐taking. The data were collected via the Maslach Burnout Inventory‐Human Services Survey (MBI‐HSS), Interpersonal Reactivity Index (IRI) measuring perspective‐taking and empathic concern, Spielberger's Professional Stress Questionnaire, and a questionnaire measuring intention to leave. Medical doctors, nurses, and psychologists working in addiction facilities were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Therefore, dealing with management and turnover became an urgent challenge for organizations and managers (Bokuchava, Javakhishvili, 2022 According to existing research literature work expectations were identified as significant reasons for job change and turnover intentions: "Work expectations regarding future work experiences as one important mechanism explaining why and how individuals (...) are less inclined to remain with their organizations. These findings suggest a process whereby systematic improvement or decrement in prior work experiences (...) shapes employees' expectations for future work experiences, which in turn influence their inclination to stay at or leave their organization" .…”
Section: Literature Backgroundmentioning
confidence: 99%
“…Therefore, dealing with management and turnover became an urgent challenge for organizations and managers (Bokuchava, Javakhishvili, 2022 According to existing research literature work expectations were identified as significant reasons for job change and turnover intentions: "Work expectations regarding future work experiences as one important mechanism explaining why and how individuals (...) are less inclined to remain with their organizations. These findings suggest a process whereby systematic improvement or decrement in prior work experiences (...) shapes employees' expectations for future work experiences, which in turn influence their inclination to stay at or leave their organization" .…”
Section: Literature Backgroundmentioning
confidence: 99%